2011
DOI: 10.1029/2011gl049548
|View full text |Cite
|
Sign up to set email alerts
|

The Mairan domes: Silicic volcanic constructs on the Moon

Abstract: The Mairan domes are four features located in northern Oceanus Procellarum at ∼312.3E, 41.4N on the Moon. High resolution visible imagery, visible‐to‐mid‐IR spectra, and Lunar Prospector Th abundance data all indicate that these four domes have a composition that is consistent with derivation from a Si‐rich, highly evolved magma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 18 publications
2
55
0
1
Order By: Relevance
“…Magmas enriched in incompatible elements (e.g., Th) typically require multiple processing episodes to form, but the observed distribution and compositional range of lunar silicic materials are difficult to explain with current models of lunar magma fractionation (e.g., Hawke et al, 20 03;Hagerty et al, 20 06;Jolliff et al, 2011Jolliff et al, , 2012Kusuma et al, 2012 ). Nevertheless, both telescopic and orbital observations of morphologically and compositionally distinct constructs, including the nearside lunar red spots (regions of strong ultraviolet (UV) absorption), have supported non-mare, Si-rich volcanic interpretations (e.g., Whitaker, 1972a;Malin, 1974;Wood and Head, 1975;Head and McCord, 1978;Müller et al, 1986;Chevrel et al, 1999;Hawke et al, 2001Hawke et al, , 2003Hagerty et al, 2006;Glotch et al, 2010;Wagner et al, 2010;Glotch et al, 2011;Jolliff et al, 2011;Kusuma et al, 2012;Lawrence et al, 2014;Wilson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 88%
“…Magmas enriched in incompatible elements (e.g., Th) typically require multiple processing episodes to form, but the observed distribution and compositional range of lunar silicic materials are difficult to explain with current models of lunar magma fractionation (e.g., Hawke et al, 20 03;Hagerty et al, 20 06;Jolliff et al, 2011Jolliff et al, , 2012Kusuma et al, 2012 ). Nevertheless, both telescopic and orbital observations of morphologically and compositionally distinct constructs, including the nearside lunar red spots (regions of strong ultraviolet (UV) absorption), have supported non-mare, Si-rich volcanic interpretations (e.g., Whitaker, 1972a;Malin, 1974;Wood and Head, 1975;Head and McCord, 1978;Müller et al, 1986;Chevrel et al, 1999;Hawke et al, 2001Hawke et al, , 2003Hagerty et al, 2006;Glotch et al, 2010;Wagner et al, 2010;Glotch et al, 2011;Jolliff et al, 2011;Kusuma et al, 2012;Lawrence et al, 2014;Wilson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 88%
“…Remote sensing studies of several lunar domes show that they have high SiO 2 , low FeO, and high Th abundances (e.g., Wilson and Head 2003;Hagerty et al 2006;Glotch et al 2010Glotch et al , 2011, consistent with the compositions of silicic lithologies found in the lunar sample suite (e.g., Papike et al 1998). The most recent results from the Diviner Lunar Radiometer Experiment on the LRO have confirmed the presence of highly silicic volcanic domes on the Moon, thus supporting the strong correlation between silica-rich lithologies and elevated Th abundances (e.g., Hagerty et al 2006;Glotch et al 2010Glotch et al , 2011.…”
Section: Compositionmentioning
confidence: 75%
“…The most recent results from the Diviner Lunar Radiometer Experiment on the LRO have confirmed the presence of highly silicic volcanic domes on the Moon, thus supporting the strong correlation between silica-rich lithologies and elevated Th abundances (e.g., Hagerty et al 2006;Glotch et al 2010Glotch et al , 2011.…”
Section: Compositionmentioning
confidence: 76%
See 2 more Smart Citations